From Ghana to America : The Skill Content of Jobs and Economic Development - Lo Bello, Salvatore; Sanchez Puerta, Maria Laura; Winkler, Hernan (World Bank, Washington, DC, 2019)
There is a growing body of literature exploring the skill content ofjobs. This article contributes to this research by using data on thetask content of occupations from developing countries, instead of US data as most existing studies do. It finds that US-based indexes do not provide a fair approximation of the levels, changes and drivers of the routine cognitive and non-routine manual skill content of jobs in developing countries. The authors also uncover three new stylized facts. First, while developed countries tend to have jobsmore intensive in non-routine cognitive skills than developing ones, income (both in growth and levels) is not associated with the skill content of jobs once other factors are accounted for. Second,while ICT adoption is linked to job de-routinization, international trade is an off setting force. Last, ICT adoption is correlated with lower employment growth in countries with a high share of occupations intensive in routine tasks.